Non-Hamiltonian molecular dynamics implementation of the Gibbs ensemble method. I. Algorithm - Bratschi, Christoph; Huber, Hanspeter (The Journal of chemical physics, 2007)
In this paper (paper I) and the following paper (paper II) [ C. Bratschi , H. Huber , and D. J. Searles , J. Chem. Phys. 126 , 164105 ( 2007 ) ], a new molecular dynamics algorithm implementing the Gibbs ensemble will be presented and then on applied to the liquid-vapor coexistence curve for two ab initio C O 2 potentials. In paper I, the Gibbs ensemble molecular dynamics algorithm using non-Hamiltonian molecular dynamics techniques is introduced. It is shown that states of the correct probability density function are sampled and the correct exchange probability is generated. The extended system Nosé-Hoover formalism is used to generate a constant temperature ensemble with equal pressures in the subsystems, combined with single particle transfers between the subsystems, over several time steps, to get equal chemical potentials.